Beam steering patch antenna using reactive loading and Yagi‐antenna concept. Issue 2 (February 2015) - Nguyen, Duy‐Thong; Siragusa, Romain; Tedjini, Smail
ABSTRACT This letter reports a technique to create beam‐steering antennas using reactive loading and passive patches. In this antenna configuration, the center patch is fed by a microstrip line and the two neighbor patches are excited through the mutual coupling from the active antenna. These two patches are loaded with a varactor diode and present a phase shift that depends on varactor capacitance. The impact of the mutual coupling on the impedance matching is investigated through a numerical calculation that combines 3D full‐wave simulation and network analysis formulas. The steering capability is enhanced by adding "director" passive patches as in the Yagi antenna principle. A prototype is designed, fabricated, and measured at UHF frequency (865–868 MHz) and shows a good agreement with the simulation. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:417–421, 2015